UAV Spectral Image Mapping of Shoreline Vegetation - Komárková, Jitka; Sedlák, Pavel (My University, 2018)
Rapid identification of a clear water surface, shoreline and vegetation can serve as a means of monitoring of the water level and as an important indicator of changes. In cases when a high level of detail or on-demand data collection is required, unmanned aerial vehicles (UAVs or ‘drones’) can provide a good service. It is important to think about the costs of the UAV and the connected sensors as well. Multispectral and thermal cameras are still very expensive in comparison to visible cameras. This article shows how a commercially available middle-class drone (DJI Phantom 3 with built-in camera), which collects data only in the visible spectral bands and is affordable even for individuals, can be easily used to calculate colour spectral indices to identify shoreline, vegetation and water.
Mapování břehové vegetace s využitím spektrálních indexů z dat UAV
Keywords: vegetation indices, UAV, low-cost monitoring; vegetační indexy, UAV, nízkonákladový monitoring